2013
DOI: 10.1111/tid.12065
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and risk factors for hepatitis B virus (HBV) reactivation after kidney transplantation in occult HBV carriers

Abstract: In conclusion, our data showed that HBV reactivation may diminish the patient survival but not graft survival. Older age and anti-T-cell antibodies may increase the risk of HBV reactivation, whereas lamivudine prophylaxis may prevent HBV reactivation after kidney transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 16 publications
0
54
0
Order By: Relevance
“…Regarding the outcome of OBI, the opposite is true for KTxR, where a reactivation of an HBV infection in HBsAg‐negative individuals under immunosuppression is of high relevance and may lead to a possibly fatal fulminant hepatitis. Data of OBI prevalence in KTxR are scarce and mostly focus on HBV reactivation rates in HBsAg‐negative patients after transplantation which have been reported to be between 0.9% and 6.5% . In a Korean study, OBI was detected in 2.3% (5/217) patients before KTx, with no HBV reactivation documented in the 36‐month follow‐up period after KTx .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the outcome of OBI, the opposite is true for KTxR, where a reactivation of an HBV infection in HBsAg‐negative individuals under immunosuppression is of high relevance and may lead to a possibly fatal fulminant hepatitis. Data of OBI prevalence in KTxR are scarce and mostly focus on HBV reactivation rates in HBsAg‐negative patients after transplantation which have been reported to be between 0.9% and 6.5% . In a Korean study, OBI was detected in 2.3% (5/217) patients before KTx, with no HBV reactivation documented in the 36‐month follow‐up period after KTx .…”
Section: Discussionmentioning
confidence: 99%
“…Data of OBI prevalence in KTxR are scarce and mostly focus on HBV reactivation rates in HBsAgnegative patients after transplantation which have been reported to be between 0.9% and 6.5%. [26][27][28] In a Korean study, OBI was detected Additional testing for HBV DNA in PBMCs has been suggested to uncover occult infections not detected by serologic methods or virus determination in serum, avoiding the potential risk of a liver biopsy. [12][13][14] Though the existence of HBV in extrahepatic tissue had been debated controversially, there is evidence that HBV can infect and replicate in PBMCs.…”
Section: Serum Only Pbmcs Only Serum + Pbmcsmentioning
confidence: 99%
“…3,4750 Reactivation of HBV replication with reappearance of HBsAg has also been reported in HBsAg-negative–anti-HBc-positive recipients of kidney transplants, although the incidence is low (0.9–5%); 51,52 however, reverse seroconversion can occur as late as 15 years after transplantation, and in some instances, correlate with a decrease in the anti-HBs titre. 51 Similar findings have been reported in heart and lung transplant recipients.…”
Section: Solid Organ Transplantationmentioning
confidence: 95%
“…Although the prevalence of HBV in patients with ESRD undergoing dialysis has decreased significantly during the past few decades [13], it remains a distinct clinical problem due to the immunosuppressive nature of renal disease that often leads to a chronic viral infection that does not occur in immunocompetent individuals. HBV infection's major clinical importance seems to be after renal transplantation, as it can cause reactivation episodes that may be severe and leading to patient's death; moreover, dialysis centers present an opportunity for pathogen transmission [14]. Therefore, the aim of this study was to investigate the prevalence of occult HBV infection in patients receiving hemodialysis at a single center in Alexandria, Egypt.…”
Section: Introductionmentioning
confidence: 99%